Knowledge and Perception of COVID-19 among School Adolescents of Lalitpur - Maharjan, Susan; Shrestha, Amrita; Shakya, Vivechana; Nepal, Manju; Thapa, Seema; Sah, Indu (Journal of Karnali Academy of Health Sciences, 2021)
Background: The world health organization declared coronavirus outbreak on 30th January 2020 and being pandemic on March 2020. It has been affecting 213 countries and territories around the world. A poor understanding of the disease among general people including school adolescents may delay seeking treatment and increase its spread. Adolescents can improve knowledge of the family members once they are well informed about disease and its prevention. Therefore, the study was conducted to identify the knowledge and perception of COVID-19 among school adolescents of Lalitpur. Methods: A cross-sectional descriptive study was carried among 305 adolescent students of purposively selected four schools. Non probability total enumerative sampling technique was used to select the sample. A self- developed self-administered structured google form questionnaire was used as instrument for data collection. Statistical Package for the Social Science (SPSS) version 16 was used for data analysis. Data analysis and interpretation was done by using descriptive statistics (frequency and percentage) and inferential statistics (Chi-square test). Results: Regarding the level of knowledge of COVID-19, 65.2 % had good knowledge, 29.2% had moderate knowledge and 5.6% had poor knowledge. Most of the students (87.2 %) had favorable perception, only 8.2% had unfavorable perception. There was significant association between age and level of knowledge (p=0.048) but no significant association with other variables. Conclusions: Nearly two third students had good knowledge and the majority of students had favorable perception toward COVID-19. However, students had lower than expected knowledge for their age; therefore awareness program is required for the school adolescent regarding COVID- 19.